PENGARUH PEMBELAJARAN DI LUAR KELAS DENGAN MODEL PROJECT BASED LEARNING TERHADAP KEMAMPUAN BERPIKIR KRITIS SISWA PADA MATERI GEOGRAFI KELAS XI DI SMA NEGERI 6 SOLOK SELATAN - KHALIL, AHMAD AL; Wilis, Ratna (JURNAL BUANA, 2024)
The purpose of this study was to explain the effect of learning outside the classroom with a project based learning model on students' critical thinking skills in class XI geography material at Senior High School Negeri 6 Solok Selatan. This study used a quasi-experimental design with two groups, namely the experimental class and the control class. The results showed a significant t-test value of 0.5% or a 95% confidence level with t count compared to t table = 12.89> 2.73 That is means that there is an influence of learning outside the classroom with the project based learning model on students' critical thinking skills in geography material for class XI iis at Senior High School country 6 south Solok . , being able to express their own opinions/be more confident and new ideas emerge. These sections have increased as a result of using the outdoor method in which there are project activities for making disaster-prone maps. These activities allow students to get facts and data that can be communicated in the results and disussion. The PJBL model section experienced improvements in both classes because students practiced what they designed. This research is suggested as an alternative learning for teachers in training students' critical thinking skills in Geography learning in class XI Senior High School.